Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Bank Perkreditan Rakyat Syariah Di Pekanbaru - Fakhri Rizqi (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was conducted at Bank Syariah Pekanbaru which is located at Jalan HR. Soebrantas, No. 105 Kel. Tuah Karya, Kec. Tampan, Pekanbaru City, Riau 28293. The purpose of this study was to determine the effect of service quality on customer satisfaction at PT Bank Perkreditan Rakyat Syariah (BPRS) Pekanbaru. To achieve this goal, a research was conducted using a sample of 99 people, using a simple random sampling method (accidental random sampling). The data analysis method used simple linear regression. Based on the results of the partial t-test test, it was found that service quality had a significant effect on customer satisfaction at PT Bank Perkreditan Rakyat Syariah (BPRS)   Pekanbaru, this was proven based on the t-test found that t-count was greater than t-table (12.645 > 1.985). The magnitude of the influence of the service quality variable on the customer satisfaction variable is 0.622 (62.2%) this is proven based on the results of the determination test where the R2 value is 0.622. Recommendations that can be submitted are expected that the company pays attention to the employees of PT Bank Perkreditan Rakyat Syariah (BPRS) Pekanbaru have expertise in using tools in the service process because this gets the lowest response from respondents.